Analisis Kualitatif dan Kuantitatif Metabolit Sekunder Ekstrak Etanol Buah Okra (Abelmoschus esculentus L. Moench) dengan Metode Spektrofotometri UV-Vis: Qualitative and Quantitative Analysis of Secondary Metabolites in Ethanol Extract of Okra (Abelmoschus esculentus L. Moench) Fruit with UV-Vis Spectrophotometry Method - Joni Tandi; Bella Melinda; Anita Purwantari; Agustinus Widodo (KOVALEN: Jurnal Riset Kimia, 2020)
This study aims to determine the content of secondary metabolites and the levels of total secondary metabolites in ethanol extract of Okra (Abelmoschus esculentus L. Moench) fruit with UV-Vis Spectrophotometry method. Okra (Abelmoschus esculentus L. Moench) fruit extract was prepared by maceration method with 96% ethanol. The extract was concentrated using a rotary evaporator that followed by a qualitative test for alkaloids, flavonoids, saponins, and tannins using suitable reagents with the test parameters, while for the qualitative assay using a UV-Vis Spectrophotometry. Qualitative analysis of alkaloids using test parameters of total alkaloids equivalent to quinine, flavonoid using parameter of total flavonoids equivalent to quercetin, saponin using parameters of standard saponins total from the Quillaja Bark, and tannin using test parameters of total tannins equivalent to tannic acid. Qualitative test results indicated that the ethanol extract of Okra fruit tested positive for alkaloids content wich characterized by the orange deposition, flavonoids characterized by the formation of an orange-yellow color, a stable foam for saponins and tannins marked in black. The quantitative analysis resulted alkaloids of 2228.06 mg/gram, flavonoids of 2.79 mg/gram, saponins of 10.03 mg/gram, and tannins of 1973.27 mg/gram. Keywords: Okra fruit, secondary metabolites, UV- Vis spectrophotometry, qualitative, quantitative.